2011
DOI: 10.1021/bm101031a
|View full text |Cite
|
Sign up to set email alerts
|

Blood Compatible Graphene/Heparin Conjugate through Noncovalent Chemistry

Abstract: Blood compatible graphene/heparin conjugate is simply formulated through noncovalent interaction between chemically reduced graphene and heparin. Charge repulsion of negatively charged heparin on graphene plates renders hydrophobic graphene to be solublized in aqueous media without any precipitation or aggregation even after 6 months. Unfractioned heparin (UFH) with higher molecular weight was effective for graphene solubilization while low molecular weight heparin (LMWH) was not. Noncovalently interacting hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(96 citation statements)
references
References 36 publications
4
91
0
1
Order By: Relevance
“…46 Despite the higher stability than lGO counterpart, considerable sediments still appeared at day 2 in the 10% serum solutions of both hGO and hGO/mPEG, owing to the intrinsically high absorption capability of GO to serum components ( Figure 1B). 9,17 Also, the noncovalent complexation with NP could effectively enhance the stability of the aqueous hGO dispersion. When the images between Figure 1B and C are compared, it was found that the PEGylation strategy proposed herein appeared to be less efficacious to stabilize hGO dispersion than that to stabilize lGO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…46 Despite the higher stability than lGO counterpart, considerable sediments still appeared at day 2 in the 10% serum solutions of both hGO and hGO/mPEG, owing to the intrinsically high absorption capability of GO to serum components ( Figure 1B). 9,17 Also, the noncovalent complexation with NP could effectively enhance the stability of the aqueous hGO dispersion. When the images between Figure 1B and C are compared, it was found that the PEGylation strategy proposed herein appeared to be less efficacious to stabilize hGO dispersion than that to stabilize lGO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results also indicate that the hydrophobic interaction between the enzymes and CRGO, in this case, is stronger than the electrostatic interaction between the enzymes and GO [94] . Similarly, Lee et al [95] reported that heparin can also be absorbed on the surface of graphene through hydrophobic interaction. They found that the hydrophobic interaction strongly depends on both electron density and geometry of heparin.…”
Section: Noncovalent Adsorption Of the Protein/ Enzyme Molecules On Tmentioning
confidence: 92%
“…189 Graphene conjugated with heparin chains preserved their anticoagulant activity, and showed a much enhanced anti-factor Xa activity of 29.6 IU/mL compared with pristine GO (1.03 IU/mL). 190 Dextran-reduced GO showed significant biocompatibility with HeLa cells, a cervical cancer cell line. 115 A study by Lee et al 191 demonstrated that graphene-and GO-coated substrates accelerated mesenchymal stem cell (MSC) adhesion, proliferation, and differentiation.…”
Section: Biocompatibility Of Graphenementioning
confidence: 96%